2022
DOI: 10.1016/j.ufug.2021.127457
|View full text |Cite
|
Sign up to set email alerts
|

Spatial statistical analysis of the relationship between self-reported mental health during the COVID-19 lockdown and closeness to green infrastructure

Abstract: The COVID-19 pandemic has produced alterations in the behaviour and psychological health of people, who have had to learn living under uncertain circumstances escaping their control. This situation has been aggravated in those countries applying strict home confinement rules to try bending their epidemic curve. This is the case of Spain, where the stringent lockdown period was extended over three months. This study aimed at proving a research hypothesis whereby living close to Green Infrastructure (GI) during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…Further studies are needed to support the variability in the proportion of alexithymic subjects following lockdown and uncover what the exact factors are. It would be interesting to study either the influence of the environment (city versus countryside) [ 46 ] or to test the hypothesis that specific groups of subjects are, more vulnerable such as healthcare professionals [ 47 ] or older people with physical disabilities [ 48 ]. Accepting the variability of the trait also implies the possibility of taking action and of treating alexithymic patients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to support the variability in the proportion of alexithymic subjects following lockdown and uncover what the exact factors are. It would be interesting to study either the influence of the environment (city versus countryside) [ 46 ] or to test the hypothesis that specific groups of subjects are, more vulnerable such as healthcare professionals [ 47 ] or older people with physical disabilities [ 48 ]. Accepting the variability of the trait also implies the possibility of taking action and of treating alexithymic patients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among our reviewed articles, twelve studies reported the nature availability indicators during COVID-19, which included the satellite-derived vegetation indices (e.g., NDVI, EVI), percentage of greenspace area, and tree canopy coverage (Cheng et al, 2021;Heo et al, 2021;Jato-Espino et al, 2022;Larson et al, 2022;Lõhmus et al, 2021;Robinson et al, 2021;Samuelsson et al, 2021;Soga et al, 2020;Vos et al, 2022;Wortzel et al, 2021;Yao et al, 2022;Zhang et al, 2022). Several studies used different satellites (e.g., Landsat-8 Operational Land Imager, Sentinel-2) with varying resolutions (e.g., 30m, 10m) at different scales (e.g., city, residence), and they used different indices.…”
Section: Nature Availabilitymentioning
confidence: 99%
“…Multiple studies assessed the percentage of greenspace area in the neighborhood. Of these, three studies measured the greenspace area as the percentage of land cover with greenspace (Jato-Espino et al, 2022;Samuelsson et al, 2021;Vos et al, 2022), where one study used the CORINE land cover map at a European scale (Jato-Espino et al, 2022), one study conducted in Belgium used orthographic images for land cover map (Vos et al, 2022) and the remaining one obtained national land cover data from Swedish Environmental Protection Agency mapped on a 10 m resolution raster during the years 2017-2019 (Samuelsson et al, 2021). Two studies estimated park area as greenspace exposure using publicly available data (Larson et al, 2022;Yao et al, 2022), such as the Statistical Yearbook of Chinese Cities 2019 (Yao et al, 2022).…”
Section: Nature Availabilitymentioning
confidence: 99%
See 2 more Smart Citations